TRADITIONAL BUILDING TECHNIQUES OF THE DRÂA VALLEY (MOROCCO) - Baglioni, Eliana; Mecca, Saveiro; Rovero, Luisa; Tonietti, Ugo (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
The present work reports the results of investigations carried out on earthen constructions in the villages of Tamnougault, Tissergat, Amzrou and Tamngrout, in the Drâa valley (Morocco). This study aims to illustrate the techniques characterizing the local building culture, in order to understand its origins and motivation. Constructions show the use of both rammed earth and adobe, used separately in different parts of the building. Floors and roofs are made with palm wood, canes and earth. The built heritage of the Drâa valley is an excellent example not only of high architecture, but also of how the local people and culture were able to respond in excellent way to the environmental challenge in a context very poor in resources.